Revealing genetic determinants of photosynthesis-related traits in citrus via genome-wide association studies - Xuesong Wang; Ryan Traband; Yoko Hiraoka; Sergio Pietro Ferrante; Lei Yu; Qiong Jia; Sarah Wang; Zixian Wang; Aleyda Acosta Rangel; Tatiane O. Vieira; Tracy L. Kahn; Mikeal L Roose; et al. (Fruit Research)
Photosynthesis-related traits, encompassing aspects such as absorbance, chlorophyll content, fluorescence, quenching ratio of incoming light, and photochemical efficiency, are pivotal characteristics directly related to photosynthesis carbon gain with important implications for overall tree physiology and fruit production. In this study, we conducted an examination of 71 citrus accessions and varieties, utilizing over 56,000 single nucleotide polymorphisms and 37 leaf reflectance parameters. Pairwise correlation analysis revealed clusters of interrelated traits organized into four distinct groups. The observed trait variations were found to have associations with the citrus phylogeny. Through genome-wide association studies, we identified a total of 125 genomic loci and 189 potentially associated genes responsible for the observed trait variations. The potential network and biological pathways influencing the variability of these biophysical variables within the citrus collection are also discussed.